Russia in the Arctic: Development plans, military potential, and conflict prevention - Michael Paul; Göran Swistek (Stiftung Wissenschaft und Politik (SWP), 2022)
Russia wants to realise a high degree of self-regulated stability in the Arctic. Moscow considers this necessary for overcoming the many problems and obstacles to development that are linked to its ambitious plans as well as the consequences of climate change. The regression of sea ice is perceived as a loss of security by the Kremlin, which reinforces its traditional siege mentality. Russian foreign policy is shaped by a reflexive priorisation of security policy above all, even in the Arctic region. Moscow tries to guarantee its national security (including economic interests) by using a broad spectrum of military build-up and corresponding strategic initiatives, which include new nuclear weapons systems. Other Arctic states as well as neighbouring countries and NATO consider these efforts a threat. Russia takes a defensive attitude in the Arctic, but it is prepared for rapid escalation in the event of confrontation. Russia's Arctic policy is a part of its strategy for exerting economic and political influence over Europe. Cooperation between its Northern and Baltic fleets is therefore increasingly important to preserve its geostrategic interests, project power and to defend its territory. The Arctic states have to perform a delicate balancing act: they want to secure sea routes and resources but avoid spiralling escalation in the region. The dialogue on military security should be revived in order to contain the consequences of the security dilemma. Opportunities for cooperation do exist, for example on climate and environmental projects, sustainable and environmentally sound energy use, infrastructure, maritime safety and security as well as economic cooperation.
Keywords: 320